Factors associated with the mask-wearing behavior of university students in Japan: a cross-sectional study of the post-mask-mandate period - Hirano, Yuko O.; Iwashita, Rin; Muta, Yuina; Ishida, Minori (Frontiers in Psychology, 2025)
The coronavirus disease 2019 (COVID-19) pandemic has required people to adapt to a new lifestyle, which includes wearing masks. In Japan, mask-wearing mandates were prolonged for nearly 3 years, leading to the habitual use of masks by many people. This habit persisted even after the relaxation of the mandates. Excessive mask wearing, such as wearing masks in low-risk settings, can lead to dehydration, especially during the summer. However, studies on Japanese people’s mask-wearing behavior in the post-mask-mandate period are lacking. Therefore, the reasons that people excessively wear masks should be investigated. This study aimed to identify factors, including perceptions of mask wearing, that influence the frequency and habit of wearing masks in the post-mandate period. An online questionnaire was distributed to 471 university students in Japan between June 12 and 24, 2023. The results indicated that the frequency of mask wearing exhibited a dichotomous trend. According to the multiple regression analysis, the strongest predictor of both the frequency and habit of mask wearing was a sense of unease from not wearing a mask rather than anxiety related to COVID-19. This study provides the government with basic data to develop guidelines for the proper wearing of masks to prevent heatstroke.